Neglected Tropical Diseases and Female Infertility: Possible Pathophysiological Mechanisms - Moses Agbomhere Hamed; Olabanji Ahmed Surakat; Victor Olukayode Ekundina; Kabirat Bolajoko Jimoh; Adetomiwa Ezekiel Adeogun; Nafisat Omolola Akanji; Oluwafemi Joshua Babalola; Patrick Chukwunonso Eya (Journal of Tropical Medicine)
Battling female infertility has posed a global challenge, where neglected tropical diseases (NTDs) are nonetheless a notable contributing factor. NTDs affect a variety of diseases, often of a chronic nature, which are often cited as some of the most lethal diseases operating against the most economically disadvantaged populations across the globe. The various causative agents for NTDs have been documented and could originate from a myriad of sources—from bacteria, fungi and viruses to ecto- and endoparasitic species—including but not limited to helminths and protozoa. This paper will seek to describe how NTDs influence female reproductive health, together with likely mediators. While these diseases have curable forms, their effects have gone well beyond female infertility, to major pain, disability and even mortality, particularly in poorer countries, thus causing economic hardship, reduced productivity and a pool of social stigma. NTDs adversely affect female reproductive functions through multiple mechanisms, including ROS-sensitive signalling, depression of steroidogenic markers and promotion of apoptosis. The effects also may reflect their influence on ovarian histomorphology, consequently resulting in female infertility. Current-directed studies, however, suggest a potential benefit in combining drugs for the most common NTDs as a deterrent to possible female infertility endowed by NTD infection. Nonetheless, further clinical investigations will be instrumental in elucidating the probable preventive value of combination drugs as adjuvant therapy to NTDs infections. This will provide comprehensive insight into the pathophysiological and molecular basis for the impairment of female fertility brought about by NTDs, leading to the development of preventive models to curb the adverse effects of NTDs on female reproductive health. Therefore, attention should be given to providing the right, timely and effective mode of treatment for NTDs-related female infertility.